The Triassic Mercia Mudstone Group: Sealing the UK's net zero future - Jonathon A. McEvoy; Richard H. Worden; Joshua Griffiths; Nicholas T. Smith; Daniel R. Faulkner; Samuel T.J. Jones; Holly J. Mills; Kevin G. Taylor (Earth-Science Reviews, 2026)

Environmental uncertainty affects movement and space-use in sheep - Sarah T. Bartsch; William H. E. J. van Wettere; Simon C. Griffith; Stephan T. Leu (Behavioral Ecology and Sociobiology, 2026)
Animals regularly experience periods of food uncertainty due to seasonal changes and environmental variability. Further, the changing climate is leading to more variable weather patterns, which alter environmental conditions, and can result in resource distributions being less predictable in space and time. How animals respond to uncertain conditions, and in particular a changing distribution of food resources, remains largely unclear and is an important question in the field of movement and animal ecology. We used an experimental approach to study how Merino sheep ( Ovis aries ) respond to different levels of food location uncertainty in a drought-impacted region of the Australian arid zone. Sheep were unfamiliar with the experimental food locations at the start and progressively decreased their uncertainty (i.e., increased their environmental knowledge) when discovering an increasing number of foraging patches. We tracked 50 sheep with GPS collars (1 location every 15 s) and deduced their movement and space use behaviour. When food uncertainty decreased, individuals moved more directionally (greater step length, smaller turn angles) and moved greater distances per day. They also had larger daily ranges. Displacement (distance between first and last location of the day) increased once and otherwise remained similar across levels of uncertainty. Our study demonstrates how an arid zone ungulate, in a large 600 ha enclosed paddock, adjusted its movement and space use behaviour as it gained environmental information on food distribution. Our study provides important insights into how animals cope with variable environments in order to forage efficiently during periods of uncertainty. Significance statement Food distributions are often unpredictable over time, with climate change exacerbating variability. Understanding how animals respond to periods of environmental uncertainty is crucial to predict animal movement in space and time. We used an experimental approach and investigated how different levels of food location uncertainty affected the movement and space-use behaviour in sheep freely moving in a large 600 ha paddock. We used the number of discovered experimental food patches as a proxy for environmental knowledge (inverse of uncertainty). Movement was faster and more directional, and daily range size increased as food uncertainty decreased and sheep gained knowledge about the food locations. Our study demonstrates how an arid zone ungulate adjusted its movement and space use behaviour as it gained environmental information about food patch distributions.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Nitrogen cycling in a high-nutrient tidal river revealed through high-resolution sampling and nitrate isotope mixing models - Josh Guyat; Douglas R. Tait; James Z. Sippo; Benjamin T. Stewart; Angus Ferguson; James A. Padilla-Montalvo; Christopher Ralph; Jenny Rogers; Merran Griffith; Dirk V. Erler; Michael Ingram; Damien T. Maher (Geochimica et Cosmochimica Acta, 2026)

Assessing the Progress of Stock Rebuilding in the Northeast Atlantic Against Levels That Can Produce Maximum Sustainable Yield - Henning Winker; Massimiliano Cardinale; Rishi Sharma; Laurence T. Kell; Iago Mosqueira; Christopher Griffiths (Fish and Fisheries, 2026)
Rebuilding fish stocks to levels above which they produce Maximum Sustainable Yield (MSY) is a management aim for all European commercially exploited stocks. Progress is typically monitored against the fishing mortality that produces MSY in the long term ( F MSY ), however, the corresponding biomass target ( B MSY ) is rarely evaluated nor reported. Here, we analyse a unique database of 73 quantitative ICES stock assessments to provide estimates of B MSY across the Northeast Atlantic and apply a Bayesian state‐space model to estimate joint trajectories of F / F MSY and B / B MSY . Our results confirm that median fishing mortality has substantially decreased from its peak in 1999 to just below F MSY in 2020. Despite this, approximately half of the stocks remain fished above F MSY , with 36% exceeding 1.2 × F MSY . Biomass increased on average from below 0.5 B MSY in 2000 to 0.68 B MSY in 2020, but only 40% of stocks are currently above B MSY and only 35% have an age structure that is comparable with fishing at F MSY . Biomass relative to the ICES trigger point (MSY B trigger ) indicates that more than 70% of stocks are currently within safe biological limits. However, using MSY B trigger as a surrogate for B MSY results in an over‐optimistic classification of stock status, which conflicts with past levels of exploitation and may hinder stock rebuilding and the achievement of MSY objectives. Future projections from individual assessment forecasts predict further increases in B / B MSY under current F levels. However, to achieve B MSY by 2030, a ‘perfect’ implementation of the ICES Advice Rule would be required.

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Using pre-release efficacy as a candidate agent prioritisation tool for the weed Trichocereus spachianus (Caryophyllales: Cactaceae) - T. C. Griffith; M. B. Aguirre; G. F. Sutton; L. Chari; I. D. Paterson (BioControl, 2025)
Pre-release efficacy assessments (PREA) can be used to prioritise the most damaging candidate agents for further studies in biological control programmes against invasive alien plants. This study assessed the efficacy of various potential enemies of Trichocereus spachianus (Riccob.) (Caryophyllales: Cactaceae), an invasive cactus in South Africa, in order to prioritise the most damaging candidates for further studies, including host specificity testing. T. spachianus is considered indigenous in Argentina and Bolivia, but the original description was based on a cultivated plant, and it is either very rare or absent in its indigenous range, with no verified records of natural populations. This necessitates the use of new associations collected off close relatives of the target plant as potential biocontrol agents. We evaluated eight potential biocontrol agents by deriving host suitability indices (HSI) and performing efficacy trials. The HSI analysis demonstrated that only one out of the eight candidate agents, a cochineal insect Dactylopius confertus De Lotto (Hemiptera: Dactylopiidae), had high fitness (high survival, fecundity and complete development) on T. spachianus . This helped us eliminate ineffective agents early on in the programme. The cochineal insect was prioritised for efficacy trials, which demonstrated its high potential efficacy, killing approximately 89% of T. spachianus plants over 60 weeks. Taken together, our results indicated that D. confertus is a highly promising potential agent for the biocontrol of T. spachianus in South Africa. By prioritising candidate biocontrol agents based on efficacy prior to host specificity testing, we ensured that the highest priority candidate agent was identified for detailed and resource-intensive host specificity testing.

Overlooked seasonal groundwater nutrient fluxes rival anthropogenic point sources across a variable land‐use tidal river - James A. Padilla‐Montalvo; Douglas R. Tait; Michael J. Reading; Benjamin T. Stewart; Angus Ferguson; Iremar Fernandez‐Vazquez; James Z. Sippo; Shivanesh Rao; Mitch Call; Christopher Ralph; Josh Guyat; Jenny Rogers; et al. (Limnology and Oceanography, 2025)
Understanding groundwater–surface water connectivity in tidal freshwater zones is essential for managing ecosystems within the riverine–estuarine continuum. Groundwater discharge is a key source of dissolved nutrient loads that can lead to eutrophication, deoxygenation, and other ecosystem imbalances in coastal environments. However, groundwater is an often‐overlooked nutrient delivery pathway, with limited studies quantifying groundwater inputs into freshwater transitional zones. Here, we quantify groundwater discharge and its associated nutrient fluxes along a ≈ 75 km section of a tidal freshwater zone within the Hawkesbury–Nepean River (New South Wales, Australia), which is surrounded by multiple land uses. High‐resolution timeseries and spatial surveys were employed over three hydrologically distinct seasons using the naturally occurring radioisotope tracer, radon. Survey results revealed decreasing surface water radon activity and nutrients toward the downstream estuarine boundary. Estimated groundwater discharge rates were highest in the upstream reaches (6.0–12.5 cm d −1 ), regardless of seasonal hydrological dynamics, and decreased downstream, aligning with a reduction in irrigation‐dependent agricultural practices and a change in adjacent catchment morphology. During the dry period, groundwater accounted for up to ≈ 68% of upstream river inputs. Groundwater discharge was also a major source of dissolved inorganic nitrogen, contributing between 0.8 and 1.1 times the inputs from local wastewater treatment plants, and up to 15 times more phosphate than upstream river sources. These findings highlight the role of groundwater discharge as a nutrient driver for tidal freshwater zones, which could have significant implications for future management strategies in these environments.

High-resolution record of global cooling during a large Mississippian positive carbon isotope excursion - Noah T. Anderson; Kristin D. Bergmann; Matthew G. Braun; Elizabeth M. Griffith; Matthew R. Saltzman (Earth and Planetary Science Letters, 2025)

Skittish Males in High Latitudes: Complex Social and Acoustic Response of Adult Male Sperm Whales When Harassed by Orcas - Mel Cosentino; Emily T. Griffiths; Jade A. van Dam; Ceres H. van Dongen (Marine Mammal Science, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Miocene marine vertebrate trophic ecology reveals megatooth sharks as opportunistic supercarnivores - Jeremy McCormack; Iris Feichtinger; Benjamin T. Fuller; Klervia Jaouen; Michael L. Griffiths; Nicolas Bourgon; Harry Maisch; Martin A. Becker; Jürgen Pollerspöck; Oliver Hampe; Gertrud E. Rössner; Alexandre Assemat; et al. (Earth and Planetary Science Letters, 2025)

Maternal Electronic Cigarette Inhalation Exposure During Gestation: Impacts on Prolactin and Xanthine Oxidase - Julie A. Griffith; Kallie J. Schafner; Krista L. Garner; Evan DeVallance; Sara E. Lewis; Timothy R. Nurkiewicz; Eric E. Kelley; Brooke A. Maxwell; William T. Goldsmith; Elizabeth C. Bowdridge (Cardiovascular Toxicology, 2025)

A summary and critique of the various spectrophotometric methods used to quantify C-phycocyanin concentration - Eric J. R. Payne; Melinda Griffiths; Susan T. L. Harrison; Marijke A. Fagan-Endres (Journal of Applied Phycology, 2025)
A wide range of research has been conducted on various applications and purification methods of C-phycocyanin (C-PC). In the published literature, there has not been consistency in the methods used to determine the concentration of C-PC within solution. This is an important characteristic to accurately determine the efficiency of a C-PC purification process and the quality of a final C-PC product. This brief report aims to critically evaluate the equations used to calculate C-PC concentration from spectrophotometric readings published in literature by discussing the logic behind the different coefficients and wavelengths used as well as by comparing the concentrations obtained for a Spirulina derived C-PC sample using the various equations. Some of the equations investigated, predominantly those which only differed slightly in the measured wavelengths, generated similar concentration results. However, these were based on work initially done on a specific cyanobacterium, Fremyella diplosiphon (Bennett and Bogorad 1973). Equations generated using other cyanobacteria extracts or even species of macroalgae generated markedly different C-PC concentrations. When these equations have been used in literature, there is often no distinction made as to whether the algal species being investigated is the same as the one used to develop the equation originally. The goal of this investigation was therefore to highlight this issue so that a more consistent and microalgal-species-appropriate approach can be used in the future for quantifying C-PC concentration in solution.

Exploring the activated charcoal adsorption column to improve cosmetic grade C-phycocyanin purification from Spirulina - Eric J. R. Payne; Melinda Griffiths; Susan T. L. Harrison; Marijke A. Fagan-Endres (Journal of Applied Phycology, 2025)
This study investigates the effectiveness of activated charcoal, a common adsorbent, in various packed column configurations in the context of a process to purify C-phycocyanin (C-PC) from Spirulina . The adsorption column performance is considered in isolation and as part of purification trains, which include chitosan treatment and ammonium sulfate precipitation. Operating parameters of interest included activated charcoal particle size, solution retention time in the column and concentration of the Spirulina crude extract used. The feed was a low purity crude extract and the final target was cosmetic grade C-PC (purity > 1.5). A slower column feed flowrate and smaller activated charcoal particle size were shown to improve the degree of C-PC purification via adsorption. Variation of the crude extract concentration did not have a significant effect. In all cases, high C-PC recoveries over the column were achieved. However, use of a single activated charcoal adsorption column was not able to purify the C-PC to cosmetic grade. Cosmetic grade purity (of between 1.68 ± 0.18 and 2.61 ± 0.44) was reached by coupling the column with chitosan treatment and ammonium sulfate precipitation when using a lower feed concentration of 2.60 ± 0.07 mg C-PC mL −1 . A higher concentration feed could not be purified to cosmetic grade within this investigation, confirming that feed concentration affects the efficiency of the activated charcoal column in combination with the other downstream process steps. The overall process had better yields and was able to accommodate a higher concentration of C-PC than reported in literature.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Ecological physiology of recovery from experimental phenology of algal food deprivation in larvae of a sea urchin (Lytechinus pictus) - Andrew W. Griffith; Ning Li; Donal T. Manahan (Marine Biology, 2025)
Studies of seasonal breeding of marine invertebrates led to many important and long-standing marine biological “Rules” (e.g., Orton; Crisp; Thorson: 1920–1950s). Currently, the world’s oceans are undergoing rapid rates of change. The extent to which these historically formative “Rules” still apply in the modern ocean is the focus of the current study. Anthropogenic-driven ocean change is altering the phenology of animal reproduction by impacting trophic mismatch of larval phases and food availability. The present study addresses these issues in larvae of the white sea urchin ( Lytechinus pictus ), an important species in marine ecology and developmental biology. Specifically, following experimentally-simulated phenological delays in the availability of phytoplankton, an integrated analysis of whole-organism, physiological, and biochemical responses revealed: (i) the limits of larval tolerance to algal food deprivation, (ii) mechanisms of nutritional stress resilience, and (iii) a higher energy cost of subsequent growth recovery once algal food became available. Contrary to expectations, unfed larvae did not deplete egg energy stores of lipid during extended periods of food deprivation. Instead, protein was the primary biochemical reserve used to fuel the metabolic cost of delayed feeding, reduced to over 80% protein depletion in unfed larvae. When algal food become available, an analysis of protein dynamics of synthesis, and turnover, and accretion showed that delayed-feeding larvae had a faster protein accretion rate. The energy cost of this compensatory catch-up strategy was, however, 2.4-fold higher. These findings highlight constraints to the classically-accepted “Rules” regarding life history strategies in a changing ocean.

Prenatal exposure to environmental bisphenols over time and their association with childhood asthma, allergic rhinitis and atopic dermatitis in the ECHO consortium - Rachel L. Miller; Yuyan Wang; Jenny Aalborg; Akram N. Alshawabkeh; Deborah H. Bennett; Carrie V. Breton; Jessie P. Buckley; Dana Dabelea; Anne L. Dunlop; Assiamira Ferrara; Griffith Gao; Abigail Gaylord; et al. (Environmental Pollution, 2025)

The Influence of Micro- and Macrocracks on the Permeability of Granite - L. Carbillet; L. Griffiths; M. J. Heap; H. Duwiquet; P. Baud; M. E. S. Violay; T. Reuschlé; L. Guillou-Frottier (Rock Mechanics and Rock Engineering, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Attentional bias to alcohol-related cues: effects of menstrual cycle phase and sex differences - Annie K. Griffith; Michelle M. Martel; Mark T. Fillmore (Psychopharmacology, 2025)

An island of receptor-like genes at the Rrs13 locus on barley chromosome 6HS co-locate with three novel sources of scald resistance - Peter E. Eckstein; Lindsay J. Griffith; Xiang M. Zhang; T. Kelly Turkington; Mark G. Colin; Samuel Holden; Sean Walkowiak; Gurcharn S. Brar; Aaron D. Beattie (Theoretical and Applied Genetics, 2024)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Cannabis use in Parkinson’s disease: Patient access to medical cannabis and physician perspective on product safety - Symone T. Griffith; Kendra D. Conrow; Michael Go; Mindy L. McEntee; Raminta Daniulaityte; Majia H. Nadesan; Mathew R. Swinburne; Holly A. Shill; Maxwell C.K. Leung (NeuroToxicology, 2024)

Integrative biological analyses of responses to food deprivation reveal resilience mechanisms in sea urchin larvae - Ning Li; Andrew W. Griffith; Donal T. Manahan (Molecular Ecology, 2024)
A fundamental question in ecology is how organisms survive food deprivation. In the ocean, climate change is impacting the phenology of food availability for early life‐history stages of animals. In this study, we undertook an integrative analysis of larvae of the sea urchin Strongylocentrotus purpuratus —an important keystone species in marine ecology and a molecular biological model organism in developmental biology. Specifically, to identify the mechanisms of resilience that maintain physiological state and the ability of organisms to recover from food deprivation, a suite of molecular biological, biochemical, physiological and whole organism measurements was completed. Previous studies focused on the importance of energy reserves to sustain larvae during periods of food deprivation. We show, however, that utilization of endogenous energy reserves only supplied 15% of the metabolic requirements of long‐term survival (up to 22 days) in the absence of particulate food. This large energy gap was not supplied by larvae feeding on bacteria. Estimates of larval ability to transport dissolved organic matter directly from seawater showed that such substrates could fully supply metabolic needs. Integrative approaches allowed for filtering of gene expression signatures, linked with gene network analyses and measured biochemical and physiological traits, to identify biomarkers of resilience. We identified 14 biomarkers related to nutrition‐responsive gene expression, of which a specific putative amino acid transporter gene was quantified in a single larva experiencing continuous nutritional stress. Advances in applications of gene expression technologies offer novel approaches to determine the physiological state of marine larval forms in ecological settings undergoing environmental change.

Rerouting of a major shipping lane through important harbour porpoise habitat caused no detectable change in annual occurrence or foraging patterns - Kylie Owen; Julia Carlström; Pia Eriksson; Mathias Andersson; Robin Nordström; Emilia Lalander; Signe Sveegaard; Line A. Kyhn; Emily T. Griffiths; Mel Cosentino; Jakob Tougaard (Marine Pollution Bulletin, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

In-situ comparison of high-order detonations and low-order deflagration methodologies for underwater unexploded ordnance (UXO) disposal - Paul A. Lepper; Sei-Him Cheong; Stephen P. Robinson; Lian Wang; Jakob Tougaard; Emily T. Griffiths; John P. Hartley (Marine Pollution Bulletin, 2024)

Differential effects of microplastic exposure on leaf shredding rates of invasive and native amphipod crustaceans - Rose M. Griffith; James W. E. Dickey; Hannah M. Williams; Jack V. Johnson; Gary Hardiman; Jaimie T. A. Dick (Biological Invasions, 2024)
There is growing concern surrounding the pervasive impacts of microplastic pollution, but despite increasing interest in this area there remains limited understanding of its disruption to biological communities and the ecosystem services they provide. One such service is the breakdown of leaf litter in freshwaters by invertebrate shredders, such as Gammarus spp. , that directly and indirectly provides resources for many other species. This study investigates the effect of microplastic exposure on leaf consumption by two Gammarus species in Ireland, the native Gammarus duebeni celticus , and the invasive Gammarus pulex . Individuals were exposed to 40–48 μm polyethylene particles for 24 h at a range of concentrations (20–200,000 MP/L), with the amount of leaf consumption in that time frame recorded. Microplastics did not affect the feeding rate of either species at environmentally relevant concentrations, indicating that ecosystem services currently provided by our study species are sustainable. However, at higher microplastic concentrations the feeding rate of G. d. celticus was significantly reduced, whereas G. pulex remained unaffected, drawing attention to species-specific and native-invader differences in microplastic impacts. The results of our study further contribute to the observed pattern that invasive species, including various amphipod species, often display a higher tolerance to environmental stressors compared to their native counterparts. This research highlights the need for mitigation of ongoing and increasing microplastic pollution that could differentially influence key ecosystem services and functions.

Remedial effectiveness of a pond biomanipulation: Habitat value and concentrations of polychlorinated biphenyls in fish - Rebecca A. Efroymson; Mark J. Peterson; R. Trent Jett; Natalie A. Griffiths; Evin T. Carter; Allison M. Fortner; Christopher R. DeRolph; Peijia Ku; Paul G. Matson; Rachel M. Pilla; Teresa J. Mathews (Journal of Hazardous Materials, 2024)

Integration of physiological and gene expression analyses to reveal biomarkers for protein dynamic mechanisms regulating higher growth and survival among larval oyster families (Crassostrea gigas) - Ning Li; Francis T.C. Pan; Andrew W. Griffith; Melissa B. DellaTorre; Donal T. Manahan (Aquaculture, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Renaming of genera Ebolavirus and Marburgvirus to Orthoebolavirus and Orthomarburgvirus, respectively, and introduction of binomial species names within family Filoviridae - Nadine Biedenkopf; Alexander Bukreyev; Kartik Chandran; Nicholas Di Paola; Pierre B. H. Formenty; Anthony Griffiths; Adam J. Hume; Elke Mühlberger; Sergey V. Netesov; Gustavo Palacios; Janusz T. Pawęska; Sophie Smither; et al. (Archives of Virology, 2023)

Atmospheric concentrations and sources of black carbon over tropical Australian waters - Changda Wu; Haydn Trounce; Erin Dunne; David W.T. Griffith; Scott D. Chambers; Alastair G. Williams; Ruhi S. Humphries; Luke T. Cravigan; Branka Miljevic; Chunlin Zhang; Hao Wang; Boguang Wang; et al. (Science of The Total Environment, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Food falls in the deep northwestern Weddell Sea - Julian B. Stauffer; Autun Purser; Huw J. Griffiths; Craig R. Smith; Henk-Jan T. Hoving (Frontiers in Marine Science, 2022)
When pelagic organisms die and fall onto the deep-sea floor they create food falls, i.e., parcels of organic enrichment that subsidize deep benthic scavenging communities. The diversity and quantities of food falls remain unstudied for many ocean regions since they are stochastically deposited and rapidly scavenged. The Southern Ocean habitat supports large populations of megafauna but few food falls have been documented. To investigate the diversity and quantity of food falls in the northwestern Weddell Sea, we analyzed 8476 images from the deep seafloor that were captured during the expedition PS118 on RV Polarstern in 2019 by the camera system OFOBS (Ocean Floor Observation and Bathymetry System). OFOBS was towed 1.5 m above the seafloor along five transects (400 to 2200 m seafloor depth) east of the Antarctic Peninsula. We observed the carcasses of one baleen whale, one penguin, and four fish at depths of 647 m, 613 m, 647 m, 2136 m, 2165 m, and 2112 m, respectively, as well as associated scavenging fauna. To the best of our knowledge, we describe here the first in situ observations of deep-sea food falls for penguins and fish in the Southern Ocean. While the whale carcass seemed in an intermediate successional stage, both the penguin and the fish were likely recently deposited and three of the fish potentially resulted from fishery discards. Our relatively small data set suggests that a diverse array of food falls provide nutrients to the slopes of the Powell Basin.

Bushfire smoke plume composition and toxicological assessment from the 2019–2020 Australian Black Summer - Jack B. Simmons; Clare Paton-Walsh; Asher P. Mouat; Jennifer Kaiser; Ruhi S. Humphries; Melita Keywood; David W. T. Griffith; Adhitya Sutresna; Travis Naylor; Jhonathan Ramirez-Gamboa (Air Quality, Atmosphere & Health, 2022)
Many of the population centres in southeast Australia were swathed in bushfire smoke during the 2019–2020 austral summer. Bushfires burning during what is now known as the Black Summer was historically large and severe, and the fire season historically long. The chemical composition in the gas and aerosol phase of aged plumes measured near Wollongong, NSW in early 2020 is reported in this work. Enhancement ratios to carbon monoxide are presented for thirteen species (acetaldehyde, acetone, acetonitrile, black carbon aerosol, benzene, methane, methacrolein + methyl vinyl ketone, methyl ethyl ketone, methanol, ammonium ion PM 1 fraction, nitrate ion PM 1 fraction, organic PM 1 fraction and PM 2.5 ). Observed plume composition is comparable to that measured in fresh smoke from Australian fires reported in the literature. Enhancements of biogenic volatile organic compounds such as isoprene (smoke-effected period mean 1 ppb, maximum 6 ppb) were observed along with elevated concentrations of particulate variables. Enhancement ratios reported here can be used in plume modelling of landscape-scale fires and assist in concentration estimates of infrequently measured atmospheric pollutants. The relative toxicological contribution of species present in the plumes was determined for plume exposure at the measurement site and for concentrated plumes at a population centre case study. Similar results were apparent at both locations. Contributions to the toxicological loading were dominated by respirable particles (~ 52–63% total contribution), formaldehyde (~ 30–39% total contribution) and acrolein. This is a reminder to consider the toxicological contributions in the gas phase when considering health impacts of population exposure to bushfire smoke.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Acoustic‐based estimates of Cuvier's beaked whale ( Ziphius cavirostris ) density and abundance along the U.S. West Coast from drifting hydrophone recorders - Jay Barlow; Jeffrey E. Moore; Jennifer L. K. McCullough; Emily T. Griffiths (Marine Mammal Science, 2022)
An acoustic survey of Cuvier's beaked whales ( Ziphius cavirostris ) was conducted off the U.S. West Coast in August and September 2016 using drifting recorder systems with a vertical array of two hydrophones at a depth of ~110 m. Recorders were deployed 22 times to representatively cover a 1,058,000 km 2 study area from the shelf break to ~556 km offshore. Vertical angles to echolocation pulses were measured using the signal time‐difference‐of‐arrival on the two hydrophones. Echolocation pulses of Cuvier's beaked whales were identified from their arrival angles (always from below the array) and unique acoustic characteristics. The density and abundance of Cuvier's beaked whales were estimated using a group‐based point‐transect analysis with 2 min time snapshots. The area effectively surveyed was estimated using a maximum simulated likelihood approach to fit the observed distribution of signal arrival angles. The acoustic availability of whales during their dive cycle was estimated from the duration of acoustic encounters using a mark‐recapture approach. Overall, Cuvier's beaked whales were present during 0.60% of snapshots, and their estimated average density is 5.12 animals per 1,000 km 2 ( CV = 0.27). Their estimated abundance in the study area is 5,454 individuals (95% credibility intervals: 3,151 to 8,907).

Maternal Nanomaterial Inhalation Exposure: Critical Gestational Period in the Uterine Microcirculation is Angiotensin II Dependent - Krista L. Garner; Elizabeth C. Bowdridge; Julie A. Griffith; Evan DeVallance; Madison G. Seman; Kevin J. Engels; Caroline P. Groth; William T. Goldsmith; Kim Wix; Thomas P. Batchelor; Timothy R. Nurkiewicz (Cardiovascular Toxicology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Evaluating the congruence between DNA ‐based and morphological taxonomic approaches in water and sediment trap samples: Analyses of a 36‐month time series from a temperate monomictic lake - Joanna Gauthier; David Walsh; Daniel T. Selbie; Alyssa Bourgeois; Katherine Griffiths; Isabelle Domaizon; Irene Gregory‐Eaves (Limnology and Oceanography, 2021)
Paleolimnological studies are central for identifying long‐term changes, yet many studies rely on bioindicators that deposit detectable subfossils in sediments, such as diatoms and cladocerans. Emerging DNA‐based approaches are expanding the taxonomic diversity that can be investigated. However, as sedimentary DNA‐based approaches are expanding rapidly, calibration work is required to determine the advantages and limitations of these techniques. In this study, we assessed the congruence between morphological and DNA‐based approaches applied to sediment trap samples for diatoms and crustaceans using both intracellular and extracellular DNA. We also evaluated which taxa are deposited in sediment traps from the water column to identify potential paleolimnological bioindicators of environmental variations. Based on 18S rRNA gene amplicons, we developed and analyzed a micro‐eukaryotic, monthly time series that spanned 3 years and was comprised of paired water column and sediment trap samples from Cultus Lake, British Columbia, Canada. Comparisons of assemblages derived from our genetic and morphological analyses using RV coefficients revealed significant correlations for diatoms, but weaker correlations for crustaceans. Intracellular DNA reads correlated more strongly with diatom morphology, while extracellular DNA reads correlated more strongly with crustacean morphology. Additional analyses of amplicon sequence variants shared between water and sediment trap samples revealed a wide diversity of taxa to study in paleolimnology, including Ciliophora, Dinoflagellata, Chytridiomycota, Chrysophyceae, and Cryptophyceae. Partial RDAs identified significant environmental predictors of these shared assemblages. Overall, our study demonstrates the effectiveness of DNA‐based approaches to track community dynamics from sediment samples, an essential step for successful paleolimnological studies.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Marine Important Bird and Biodiversity Areas for Penguins in Antarctica, Targets for Conservation Action - Jonathan Handley; Marie-Morgane Rouyer; Elizabeth J. Pearmain; Victoria Warwick-Evans; Katharina Teschke; Jefferson T. Hinke; Heather Lynch; Louise Emmerson; Colin Southwell; Gary Griffith; César A. Cárdenas; Aldina M. A. Franco; et al. (Frontiers in Marine Science, 2021)
Global targets for area-based conservation and management must move beyond threshold-based targets alone and must account for the quality of such areas. In the Southern Ocean around Antarctica, a region where key biodiversity faces unprecedented risks from climate change and where there is a growing demand to extract resources, a number of marine areas have been afforded enhanced conservation or management measures through two adopted marine protected areas (MPAs). However, evidence suggests that additional high quality areas could benefit from a proposed network of MPAs. Penguins offer a particular opportunity to identify high quality areas because these birds, as highly visible central-place foragers, are considered indicator species whose populations reflect the state of the surrounding marine environment. We compiled a comprehensive dataset of the location of penguin colonies and their associated abundance estimates in Antarctica. We then estimated the at-sea distribution of birds based on information derived from tracking data and through the application of a modified foraging radius approach with a density decay function to identify some of the most important marine areas for chick-rearing adult penguins throughout waters surrounding Antarctica following the Important Bird and Biodiversity Area (IBA) framework. Additionally, we assessed how marine IBAs overlapped with the currently adopted and proposed network of key management areas (primarily MPAs), and how the krill fishery likely overlapped with marine IBAs over the past five decades. We identified 63 marine IBAs throughout Antarctic waters and found that were the proposed MPAs to be adopted, the permanent conservation of high quality areas for penguin species would increase by between 49 and 100% depending on the species. Furthermore, our data show that, despite a generally contracting range of operation by the krill fishery in Antarctica over the past five decades, a consistently disproportionate amount of krill is being harvested within marine IBAs compared to the total area in which the fishery operates. Our results support the designation of the proposed MPA network and offer additional guidance as to where decision-makers should act before further perturbation occurs in the Antarctic marine ecosystem.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Applying the zoo model to conservation of threatened exceptional plant species - Jordan Wood; Jonathan D. Ballou; Taylor Callicrate; Jeremie B. Fant; M. Patrick Griffith; Andrea T. Kramer; Robert C. Lacy; Abby Meyer; Sara Sullivan; Kathy Traylor‐Holzer; Seana K. Walsh; Kayri Havens (Conservation Biology, 2020)
Maintaining a living plant collection is the most common method of ex situ conservation for plant species that cannot be seed banked (i.e., exceptional species). Viability of living collections, and their value for future conservation efforts, can be limited without coordinated efforts to track and manage individuals across institutions. Using a pedigree‐focused approach, the zoological community has established an inter‐institutional infrastructure to support long‐term viability of captive animal populations. We assessed the ability of this coordinated metacollection infrastructure to support the conservation of 4 plant species curated in living collections at multiple botanic gardens around the world. Limitations in current practices include the inability to compile, share, and analyze plant collections data at the individual level, as well as difficulty in tracking original provenance of ex situ material. The coordinated metacollection framework used by zoos can be adopted by the botanical community to improve conservation outcomes by minimizing the loss of genetic diversity in collections. We suggest actions to improve ex situ conservation of exceptional plant species, including developing a central database to aggregate data and track unique individuals of priority threatened species among institutions and adapting a pedigree‐based population management tool that incorporates life‐history aspects unique to plants. If approached collaboratively across regional, national, and global scales, these actions could transform ex situ conservation of threatened plant species.

Effect of carbohydrate–protein supplementation on endurance training adaptations - Abdullah F. Alghannam; Iain Templeman; Joel E. Thomas; Dawid Jedrzejewski; Samuel Griffiths; Joseph Lemon; Thomas Byers; Sue Reeves; Javier T. Gonzalez; Dylan Thompson; James Bilzon; Kostas Tsintzas; et al. (European Journal of Applied Physiology, 2020)
Purpose To examine the influence of post-exercise protein feeding upon the adaptive response to endurance exercise training. Methods In a randomised parallel group design, 25 healthy men and women completed 6 weeks of endurance exercise training by running on a treadmill for 30–60 min at 70–75% maximal oxygen uptake ( V O 2max ) 4 times/week. Participants ingested 1.6 g per kilogram of body mass (g kg BM −1 ) of carbohydrate (CHO) or an isocaloric carbohydrate–protein solution (CHO-P; 0.8 g carbohydrate kg BM −1 + 0.8 g protein kg BM −1 ) immediately and 1 h post-exercise. Expired gas, blood and muscle biopsy samples were taken at baseline and follow-up. Results Exercise training improved V O 2max in both groups ( p ≤ 0.001), but this increment was not different between groups either in absolute terms or relative to body mass (0.2 ± 0.2 L min −1 and 3.0 ± 2 mL kg −1 min −1 , respectively). No change occurred in plasma albumin concentration from baseline to follow-up with CHO-P (4.18 ± 0.18 to 4.23 ± 0.17 g dL −1 ) or CHO (4.17 ± 0.17 to 4.12 ± 0.22 g dL −1 ; interaction: p > 0.05). Mechanistic target of rapamycin (mTOR) gene expression was up-regulated in CHO-P (+ 46%; p = 0.025) relative to CHO (+ 4%) following exercise training. Conclusion Post-exercise protein supplementation up-regulated the expression of mTOR in skeletal muscle over 6 weeks of endurance exercise training. However, the magnitude of improvement in V O 2max was similar between groups.

Soil nutrients and precipitation are major drivers of global patterns of grass leaf silicification - Kathleen M. Quigley; Daniel M. Griffith; George L. Donati; T. Michael Anderson (Ecology, 2020)
Grasses accumulate high concentrations of silicon (Si) in their tissues, with potential benefits including herbivore defense, improved water balance, and reduced leaf construction costs. Although Si is one of the most widely varying leaf constituents among individuals, species, and ecosystems, the environmental forces driving this variation remain elusive and understudied. To understand relationships between environmental factors and grass Si accumulation better, we analyzed foliar chemistry of grasses from 17 globally distributed sites where nutrient inputs and grazing were manipulated. These sites span natural gradients in temperature, precipitation, and underlying soil properties, which allowed us to assess the relative importance of soil moisture and nutrients across variation in climate. Foliar Si concentration did not respond to large mammalian grazer exclusion, but significant variation in herbivore abundance among sites may have precluded the observation of defoliation effects at these sites. However, nutrient addition consistently reduced leaf Si, especially at sites with low soil nitrogen prior to nutrient addition. Additionally, a leaf‐level trade‐off between Si and carbon (C) existed that was stronger at arid sites than mesic sites. Our results suggest soil nutrient limitation favors investment in Si over C‐based leaf construction, and that fixing C is especially costly relative to assimilating Si when water is limiting. Our results demonstrate the importance of soil nutrients and precipitation as key drivers of global grass silicification patterns.

Triassic to Neogene tectono-magmatic events within Lorne Basin evolution, coastal New South Wales, eastern Australia - F. L. Sutherland; I. T. Graham; H. Zwingmann; D. J. Och; C. J. Gardner; R. E. Pogson; R. J. Griffiths; A. Lay (Australian Journal of Earth Sciences, 2020)

Trajectories of body mass index, from adolescence to older adulthood, and pancreatic cancer risk; a population-based case–control study in Ontario, Canada - Vanessa De Rubeis; Michelle Cotterchio; Brendan T. Smith; Lauren E. Griffith; Ayelet Borgida; Steven Gallinger; Sean Cleary; Laura N. Anderson (Cancer Causes & Control, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Description of a new beaked whale echolocation pulse type in the California Current - Emily T. Griffiths; Jennifer L. Keating; Jay Barlow; Jeffrey E. Moore (Marine Mammal Science, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Can houseplants improve indoor air quality by removing CO2 and increasing relative humidity? - C. Gubb; T. Blanusa; A. Griffiths; C. Pfrang (Air Quality, Atmosphere & Health, 2018)

Potentially infanticidal behavior in the Amazon river dolphin (Inia geoffrensis) - Mark T. Bowler; Brian M. Griffiths; Michael P. Gilmore; Andrew Wingfield; Maribel Recharte (acta ethologica, 2018)

Low genetic variation between South American and Antarctic populations of the bank-forming moss Chorisodontium aciphyllum (Dicranaceae) - E. M. Biersma; J. A. Jackson; T. J. Bracegirdle; H. Griffiths; K. Linse; P. Convey (Polar Biology, 2018)

Herbivory and eutrophication mediate grassland plant nutrient responses across a global climatic gradient - T. Michael Anderson; Daniel M. Griffith; James B. Grace; Eric M. Lind; Peter B. Adler; Lori A. Biederman; Dana M. Blumenthal; Pedro Daleo; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; Andrew S. MacDougall; et al. (Ecology, 2018)
Plant stoichiometry, the relative concentration of elements, is a key regulator of ecosystem functioning and is also being altered by human activities. In this paper we sought to understand the global drivers of plant stoichiometry and compare the relative contribution of climatic vs. anthropogenic effects. We addressed this goal by measuring plant elemental (C, N, P and K) responses to eutrophication and vertebrate herbivore exclusion at eighteen sites on six continents. Across sites, climate and atmospheric N deposition emerged as strong predictors of plot‐level tissue nutrients, mediated by biomass and plant chemistry. Within sites, fertilization increased total plant nutrient pools, but results were contingent on soil fertility and the proportion of grass biomass relative to other functional types. Total plant nutrient pools diverged strongly in response to herbivore exclusion when fertilized; responses were largest in ungrazed plots at low rainfall, whereas herbivore grazing dampened the plant community nutrient responses to fertilization. Our study highlights (1) the importance of climate in determining plant nutrient concentrations mediated through effects on plant biomass, (2) that eutrophication affects grassland nutrient pools via both soil and atmospheric pathways and (3) that interactions among soils, herbivores and eutrophication drive plant nutrient responses at small scales, especially at water‐limited sites.

Relatedness and body size influence territorial behaviour in Salmo salar juveniles in the wild - W. P. A. Fernandes; S. W. Griffiths; A. T. Ibbotson; W. D. Riley (Fisheries Management and Ecology, 2017)
Wild Atlantic salmon, Salmo salar L., juveniles defend territories to enable exclusive access to food resources, and kin selection benefits may be accrued where territorial boundaries of relatives overlap. This study explored space sharing events between pairs of sibling and non‐sibling fish as a measure of territoriality and resource competition in a small chalk stream using passive integrated transponder ( PIT ) technology. The time period between fish detections in a shared space was closer between pairs of siblings (sibling pairs mean = 60.48 ± 51.84 min; non‐sibling pairs mean = 348.8 ±65.94 min). These results suggest that the territorial boundaries of related fish often overlap, thus increasing the likelihood of siblings accruing kin selection benefits. The findings from this study also suggest that outcomes of competitive interactions among dominant and subordinate fish are less pronounced when fish are related.

Arteriosclerosis in the ventral aorta and epicarditis in the bulbus arteriosus of Atlantic salmon ( Salmo salar L) - A S Dalum; K H Kristthorsdottir; D J Griffiths; K Bjørklund; T T Poppe (Journal of Fish Diseases, 2017)
Spontaneous mortality of seemingly healthy, farmed Atlantic salmon ( Salmo salar L) is an increasing problem in Norwegian aquaculture. In this study, we present a morphological study of the previously undescribed syndrome of arteriosclerosis of the ventral aorta and epicarditis of the adjacent bulbus arteriosus found in farmed Atlantic salmon, with wild‐captured fish as a control group. Both the ventral aorta and epicardium are vital for correct arterial compliance and vascular resistance in the respiratory capillaries of the gills. We discuss the possible implications of ventral aorta arteriosclerosis and epicarditis for blood vascular health and in particular for the increasing frequency of spontaneous gill bleeding in farmed salmon. As both these conditions primarily occur in farmed salmon, we suggest that they should be considered pathological.

Leaf thickness controls variation in leaf mass per area (LMA) among grazing-adapted grasses in Serengeti - Daniel M. Griffith; Kathleen M. Quigley; T. Michael Anderson (Oecologia, 2016)

Planning adaptation to climate change in fast-warming marine regions with seafood-dependent coastal communities - Alistair J. Hobday; Kevern Cochrane; Nicola Downey-Breedt; James Howard; Shankar Aswani; Val Byfield; Greg Duggan; Elethu Duna; Leo X. C. Dutra; Stewart D. Frusher; Elizabeth A. Fulton; Louise Gammage; et al. (Reviews in Fish Biology and Fisheries, 2016)

Differences in soil micro‐eukaryotic communities over soil pH gradients are strongly driven by parasites and saprotrophs - A. Ö. C. Dupont; R. I. Griffiths; T. Bell; D. Bass (Environmental Microbiology, 2016)
Summary A recent large‐scale assessment of bacterial communities across a range of UK soil types showed that bacterial community structure was strongly determined by soil pH. We analysed a data set of eukaryotic 454 sequencing 18S rDNA from the surveyed samples and showed significant differences in eukaryotic assemblages according to pH class, mostly between low pH and higher pH soils. Soil eukaryote communities (per sample) differed most at the taxonomic rank approximating to order level. Taxonomies assigned with the P rotist R ibosomal R eference and the S ilva 119 databases were taxonomically inconsistent, mostly due to differing 18S annotations, although general structure and composition according to pH were coherent. A relatively small number of lineages, mostly putative parasitic protists and fungi, drive most differences between pH classes, with weaker contributions from bacterivores and autotrophs. Overall, soil parasites included a large diversity of alveolates, in particular apicomplexans. Phylogenetic analysis of alveolate lineages demonstrates a large diversity of unknown gregarines, novel perkinsids, coccidians, colpodellids and uncharacterized alveolates. Other novel and/or divergent lineages were revealed across the eukaryote tree of life. Our study provides an in‐depth taxonomic evaluation of micro‐eukaryotic diversity, and reveals novel lineages and insights into their relationships with environmental variables across soil gradients.

Anaerobic digestion of Spirulina sp. and Scenedesmus sp.: a comparison and investigation of the impact of mechanical pre-treatment - A. E. Inglesby; M. J. Griffiths; S. T. L. Harrison; R. P. van Hille (Journal of Applied Phycology, 2015)

Assessing the influence of topography and canopy structure on Douglas fir throughfall with LiDAR and empirical data in the Santa Cruz mountains, USA - K. T. Griffith; A. G. Ponette-González; L. M. Curran; K. C. Weathers (Environmental Monitoring and Assessment, 2015)

Maximizing the phylogenetic diversity of seed banks - Kate E. Griffiths; Sharon T. Balding; John B. Dickie; Gwilym P. Lewis; Tim R. Pearce; Richard Grenyer (Conservation Biology, 2015)
Ex situ conservation efforts such as those of zoos, botanical gardens, and seed banks will form a vital complement to in situ conservation actions over the coming decades. It is therefore necessary to pay the same attention to the biological diversity represented in ex situ conservation facilities as is often paid to protected‐area networks. Building the phylogenetic diversity of ex situ collections will strengthen our capacity to respond to biodiversity loss. Since 2000, the Millennium Seed Bank Partnership has banked seed from 14% of the world's plant species. We assessed the taxonomic, geographic, and phylogenetic diversity of the Millennium Seed Bank collection of legumes (Leguminosae). We compared the collection with all known legume genera, their known geographic range (at country and regional levels), and a genus‐level phylogeny of the legume family constructed for this study. Over half the phylogenetic diversity of legumes at the genus level was represented in the Millennium Seed Bank. However, pragmatic prioritization of species of economic importance and endangerment has led to the banking of a less‐than‐optimal phylogenetic diversity and prioritization of range‐restricted species risks an underdispersed collection. The current state of the phylogenetic diversity of legumes in the Millennium Seed Bank could be substantially improved through the strategic banking of relatively few additional taxa. Our method draws on tools that are widely applied to in situ conservation planning, and it can be used to evaluate and improve the phylogenetic diversity of ex situ collections. Maximizar la Riqueza Filogenética de los Bancos de Semillas

Biogeographically distinct controls on C 3 and C 4 grass distributions: merging community and physiological ecology - Daniel M. Griffith; T. Michael Anderson; Colin P. Osborne; Caroline A. E. Strömberg; Elisabeth J. Forrestel; Christopher J. Still (Global Ecology and Biogeography, 2015)
Aim C 4 photosynthesis is an adaptation that maintains efficient carbon assimilation in high‐light, high‐temperature conditions. Due to the importance of C 4 grasses for carbon and surface energy fluxes, numerous models have been proposed to describe their spatial distribution and forecast their responses to climate change. These models often rely on broad climatic predictors (e.g. temperature and precipitation) but fail to integrate other ecologically relevant factors like disturbance and competition, which may modify realized C 3 / C 4 grass distributions. Here, we present a combined evaluation of the contribution of ecological factors and climatic predictors to realized C 3 / C 4 grass distributions. We consider multiple biogeographic regions of N orth A merica using a multisource database of over 40,000 vegetation plots. Location The conterminous U nited S tates of A merica ( USA ). Methods We identified a comprehensive pool of climatic models in the literature and used information theoretic criteria to select a primary climatic predictor of C 3 and C 4 grass distributions. Subsequently, the best model was combined with ecological predictors (e.g. fire, tree cover) using a multiple regression framework and tested within eight regions. Results Surprisingly, grass‐dominated communities across the USA exist largely in C 3 ‐ or C 4 ‐dominated states. Transitions between C 3 / C 4 dominance were best explained by models that integrated temperature and precipitation with ecological factors that varied according to region. For some regions, like E astern T emperate F orests, local ecological factors were comparable in strength to broad‐scale climatic predictors of C 3 / C 4 abundance. Main conclusion Local ecological factors modify C 3 / C 4 grass responses to broad‐scale climatic drivers in ways that manifest at regional scales. In E astern T emperate F orests, for example, C 4 grass abundances are maintained below climatic expectations where tree cover creates light limitation but above expectations where frequent fires reduce tree cover. Thus, local ecological factors, which vary among biogeographic regions, contribute to large‐scale climate disequilibrium.

Investigating the influence of aquifer heterogeneity on the potential for thermal free convection in the Yarragadee Aquifer, Western Australia - Dylan J. Irvine; Heather A. Sheldon; Craig T. Simmons; Adrian D. Werner; Cedric M. Griffiths (Hydrogeology Journal, 2015)

Localization of submicron inclusion re-equilibration at healed fractures in host garnet - T. A. Griffiths; G. Habler; D. Rhede; R. Wirth; F. Ram; R. Abart (Contributions to Mineralogy and Petrology, 2014)

Proximity to ice fields and lake depth as modulators of paleoclimate records: a regional study from southwest Yukon, Canada - Guangjie Chen; Daniel T. Selbie; Katherine Griffiths; Jon N. Sweetman; Morgan Botrel; Zofia E. Taranu; Sébastien Knops; Jennifer Bondy; Neal Michelutti; John P. Smol; Irene Gregory-Eaves (Journal of Paleolimnology, 2014)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Reproductive biology of wahoo, Acanthocybium solandri, off eastern Australia - Mitchell T. Zischke; Jessica H. Farley; Shane P. Griffiths; Ian R. Tibbetts (Reviews in Fish Biology and Fisheries, 2013)

Genetic Diversity and Population Structure Among Oat Cultivars and Landraces - G. Montilla-Bascón; J. Sánchez-Martín; N. Rispail; D. Rubiales; L. Mur; T. Langdon; I. Griffiths; C. Howarth; E. Prats (Plant Molecular Biology Reporter, 2013)

Towards a unified paradigm for sequence‐based identification of fungi - Urmas Kõljalg; R. Henrik Nilsson; Kessy Abarenkov; Leho Tedersoo; Andy F. S. Taylor; Mohammad Bahram; Scott T. Bates; Thomas D. Bruns; Johan Bengtsson‐Palme; Tony M. Callaghan; Brian Douglas; Tiia Drenkhan; et al. (Molecular Ecology, 2013)
The nuclear ribosomal internal transcribed spacer ( ITS ) region is the formal fungal barcode and in most cases the marker of choice for the exploration of fungal diversity in environmental samples. Two problems are particularly acute in the pursuit of satisfactory taxonomic assignment of newly generated ITS sequences: (i) the lack of an inclusive, reliable public reference data set and (ii) the lack of means to refer to fungal species, for which no Latin name is available in a standardized stable way. Here, we report on progress in these regards through further development of the UNITE database ( http://unite.ut.ee ) for molecular identification of fungi. All fungal species represented by at least two ITS sequences in the international nucleotide sequence databases are now given a unique, stable name of the accession number type (e.g. H ymenoscyphus pseudoalbidus | GU 586904| SH 133781.05 FU ), and their taxonomic and ecological annotations were corrected as far as possible through a distributed, third‐party annotation effort. We introduce the term ‘species hypothesis’ ( SH ) for the taxa discovered in clustering on different similarity thresholds (97–99%). An automatically or manually designated sequence is chosen to represent each such SH. These reference sequences are released ( http://unite.ut.ee/repository.php ) for use by the scientific community in, for example, local sequence similarity searches and in the QIIME pipeline. The system and the data will be updated automatically as the number of public fungal ITS sequences grows. We invite everybody in the position to improve the annotation or metadata associated with their particular fungal lineages of expertise to do so through the new Web‐based sequence management system in UNITE .

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Efficacy of novel sampling approaches for surveying specialised recreational fisheries - Shane P. Griffiths; Mitchell T. Zischke; Mark L. Tonks; Julian G. Pepperell; Sharon Tickell (Reviews in Fish Biology and Fisheries, 2013)

Dispersal patterns and population structuring among platypuses, Ornithorhynchus anatinus, throughout south-eastern Australia - E. M. Furlan; J. Griffiths; N. Gust; K. A. Handasyde; T. R. Grant; B. Gruber; A. R. Weeks (Conservation Genetics, 2013)

Agricultural land use alters the seasonality and magnitude of stream metabolism - Natalie A. Griffiths; Jennifer L. Tank; Todd V. Royer; Sarah S. Roley; Emma J. Rosi-Marshall; Matt R. Whiles; Jake J. Beaulieu; Laura T. Johnson (Limnology and Oceanography, 2013)
We present a comprehensive data set of gross primary production (GPP) and ecosystem respiration (ER) in open‐canopy, nutrient‐rich streams draining row‐crop agriculture in the midwestern United States. We used two approaches to characterize temporal and spatial variation in whole‐stream metabolism: continuous measurements in one agricultural stream for 1 yr, and periodic daily measurements in six agricultural streams on six dates spanning summer, autumn, and winter. Continuous measurements revealed high rates of GPP (range: 0.1 to 22.0 g O 2 m −2 d −1 ) and ER (range: −0.9 to −34.8 g O 2 m −2 d −1 ) that varied seasonally with light availability and temperature. GPP and ER were correlated during periods of high autotrophic production, suggesting that autotrophic respiration comprised a large portion of ER; however, the GPP : ER ratio exceeded 1 for only 4% of the year. While there were distinct temporal patterns in metabolism in one agricultural stream, rates of GPP and ER were similar among six streams when assessed via periodic daily measurements, and 26% of all periodic daily measurements were autotrophic with GPP : ER > 1. However, these periodic measurements were collected under baseflow conditions and may have overestimated the extent of autotrophy in agricultural streams. Overall, the open canopy and elevated nutrients of agricultural streams resulted in higher rates of GPP and ER compared with more pristine systems. Estimates of metabolism are needed from underrepresented systems to accurately quantify carbon fluxes from fluvial ecosystems.

Effects of trawling on the diets of common demersal fish by‐catch of a tropical prawn trawl fishery - Q. Dell; S. P. Griffiths; M. L. Tonks; W. A. Rochester; M. J. Miller; M. A. Duggan; T. D. van der Velde; R. D. Pillans; G. J. Coman; R. H. Bustamante; D. A. Milton (Journal of Fish Biology, 2013)
The ecological effect of prawn trawling on the benthos of the Gulf of Carpentaria, northern Australia, was investigated by examining stomach contents of common demersal fishes incidentally caught as by‐catch in the fishery. Fishes were collected from high and low fishing intensity sites in three regions based on vessel monitoring system data. The diets of eight species of benthic fish predators were compared between regions and fishing intensities. A regional effect on diet was evident for seven species. Only one generalist species had no significant difference in diet among the three regions. For the comparisons within each region, five predator species had significantly different diet between high and low fishing intensities in at least one region. Across the three regions, high fishing intensity sites had predators that consumed a greater biomass of crustaceans, molluscs and echinoderms. At low fishing intensity sites, predators had diets comprising a greater biomass of cnidarians and teleosts, and a different assemblage of molluscs, crustaceans and fishes. These changes in diet suggest that there may have been a shift in the structure of the benthic community following intensive fishing. Analysis of predator diets is a useful tool to help identify changes in the benthic community composition after exposure to fishing. This study also provided valuable diet information on a range of abundant generalist benthic predators to improve the ecosystem modelling tools needed to support ecosystem‐based fisheries management.

Lipid productivity, settling potential and fatty acid profile of 11 microalgal species grown under nitrogen replete and limited conditions - Melinda J. Griffiths; Robert P. van Hille; Susan T. L. Harrison (Journal of Applied Phycology, 2012)

Multilayer thin-film coatings capable of extended programmable drug release: application to human mesenchymal stem cell differentiation - Jinkee Hong; Luis M. Alvarez; Nisarg J. Shah; Younghyun Cho; Byeong-Su Kim; Linda G. Griffith; Kookheon Char; Paula T. Hammond (Drug Delivery and Translational Research, 2012)

Changes in the choice of colorectal cancer screening tests in primary care settings from 7,845 prospectively collected surveys - Martin C. S. Wong; George K. John; Hoyee W. Hirai; Thomas Y. T. Lam; Arthur K. C. Luk; Jessica Y. L. Ching; Simon S. M. Ng; Francis K. L. Chan; Sian M. Griffiths; Joseph J. Y. Sung (Cancer Causes & Control, 2012)

Development of an eight gene expression profile implicating human breast tumours of all grade - P. N. Gabrovska; R. A. Smith; T. Tiang; S. R. Weinstein; L. M. Haupt; L. R. Griffiths (Molecular Biology Reports, 2012)

Erratum to: Molecular characterization of the translocation breakpoints in the Down syndrome mouse model Ts65Dn - Laura G. Reinholdt; Yueming Ding; Griffith J. Gilbert; Anne Czechanski; Jeffrey P. Solzak; Randall J. Roper; Mark T. Johnson; Leah Rae Donahue; Cathleen Lutz; Muriel T. Davisson (Mammalian Genome, 2011)

Molecular characterization of the translocation breakpoints in the Down syndrome mouse model Ts65Dn - Laura G. Reinholdt; Yueming Ding; Griffith T. Gilbert; Anne Czechanski; Jeffrey P. Solzak; Randall J. Roper; Mark T. Johnson; Leah Rae Donahue; Cathleen Lutz; Muriel T. Davisson (Mammalian Genome, 2011)

Effectiveness of GIS suitability mapping in predicting ecological impacts of proposed wind farm development on Aristazabal Island, BC - James C. Griffiths; William T. Dushenko (Environment, Development and Sustainability, 2011)

Transport of NOX Emissions from Sugarcane Fertilisation into the Great Barrier Reef Lagoon - Clare Paton-Walsh; Stephen R. Wilson; Travis Naylor; David W. T. Griffith; O. T. Denmead (Environmental Modeling & Assessment, 2011)

Revealing the scale of marine bioinvasions in developing regions: a South African re-assessment - A. Mead; J. T. Carlton; C. L. Griffiths; M. Rius (Biological Invasions, 2011)

Microsatellite standardization and evaluation of genotyping error in a large multi-partner research programme for conservation of Atlantic salmon (Salmo salar L.) - J. S. Ellis; J. Gilbey; A. Armstrong; T. Balstad; E. Cauwelier; C. Cherbonnel; S. Consuegra; J. Coughlan; T. F. Cross; W. Crozier; E. Dillane; D. Ensing; et al. (Genetica, 2011)

Effects of simultaneous climate change and geomorphic evolution on thermal characteristics of a shallow Alaskan lake - Jennifer R. Griffiths; Daniel E. Schindler; Laurie S. Balistrieri; Gregory T. Ruggerone (Limnology and Oceanography, 2011)
We used a hydrodynamics model to assess the consequences of climate warming and contemporary geomorphic evolution for thermal conditions in a large, shallow Alaskan lake. We evaluated the effects of both known climate and landscape change, including rapid outlet erosion and migration of the principal inlet stream, over the past 50 yr as well as future scenarios of geomorphic restoration. Compared to effects of air temperature during the past 50 yr, lake thermal properties showed little sensitivity to substantial (~60%) loss of lake volume, as the lake maximum depth declined from 6 m to 4 m driven by outlet erosion. The direction and magnitude of future lake thermal responses will be driven largely by the extent of inlet stream migration when it occurs simultaneously with outlet erosion. Maintaining connectivity with inlet streams had substantial effects on buffering lake thermal responses to warming climate. Failing to account for changing rates and types of geomorphic processes under continuing climate change may misidentify the primary drivers of lake thermal responses and reduce our ability to understand the consequences for aquatic organisms.

Effects of climate‐driven primary production change on marine food webs: implications for fisheries and conservation - C. J. BROWN; E. A. FULTON; A. J. HOBDAY; R. J. MATEAR; H. P. POSSINGHAM; C. BULMAN; V. CHRISTENSEN; R. E. FORREST; P. C. GEHRKE; N. A. GRIBBLE; S. P. GRIFFITHS; H. LOZANO‐MONTES; et al. (Global Change Biology, 2010)
Climate change is altering the rate and distribution of primary production in the world's oceans. Primary production is critical to maintaining biodiversity and supporting fishery catches, but predicting the response of populations to primary production change is complicated by predation and competition interactions. We simulated the effects of change in primary production on diverse marine ecosystems across a wide latitudinal range in Australia using the marine food web model Ecosim. We link models of primary production of lower trophic levels (phytoplankton and benthic producers) under climate change with Ecosim to predict changes in fishery catch, fishery value, biomass of animals of conservation interest, and indicators of community composition. Under a plausible climate change scenario, primary production will increase around Australia and generally this benefits fisheries catch and value and leads to increased biomass of threatened marine animals such as turtles and sharks. However, community composition is not strongly affected. Sensitivity analyses indicate overall positive linear responses of functional groups to primary production change. Responses are robust to the ecosystem type and the complexity of the model used. However, model formulations with more complex predation and competition interactions can reverse the expected responses for some species, resulting in catch declines for some fished species and localized declines of turtle and marine mammal populations under primary productivity increases. We conclude that climate‐driven primary production change needs to be considered by marine ecosystem managers and more specifically, that production increases can simultaneously benefit fisheries and conservation. Greater focus on incorporating predation and competition interactions into models will significantly improve the ability to identify species and industries most at risk from climate change.

Re-evaluating blue mussel depuration rates in ‘Dynamics of the phycotoxin domoic acid: accumulation and excretion in two commercially important bivalves’ - Finn T. O. Krogstad; William C. Griffith; Eric M. Vigoren; Elaine M. Faustman (Journal of Applied Phycology, 2009)

Quantifying the metabolic cost to an Antarctic liverwort of responding to an abrupt increase in UVB radiation exposure - K. R. S. SNELL; T. KOKUBUN; H. GRIFFITHS; P. CONVEY; D. A. HODGSON; K. K. NEWSHAM (Global Change Biology, 2009)
We quantified the metabolic cost to the Antarctic leafy liverwort Cephaloziella varians of responding to an abrupt increase in ultraviolet B (UVB) radiation exposure in the natural environment at Rothera Point on the western Antarctic Peninsula (67 °34′S, 68 °07′W). The liverwort was protected from exposure to UVB radiation for 44 days with screens containing Mylar polyester, after which time its thalli, which are normally black in colour, had become green owing to reduced concentrations of an anthocyanidin, identified here as riccionidin A, in thallus tips. Thalli were then exposed to an abrupt increase in UVB radiation by removing the screens. The thalli became visibly darker within 48 h of the screens being removed, resynthesizing riccionidin A to the same concentration as that present in thalli outside screens during this period. Chlorophyll fluorescence measurements indicated that nonphotochemical quenching was higher in the thalli formerly under the screens than in those not previously covered with screens, but that F v / F m and photochemical quenching were the same in the two groups of thalli. We used data from aqueous phase oxygen electrode measurements to calculate an estimate for carbon fixation by C. varians during the 48 h after the screens were removed. Assuming a photosynthetic quotient for Antarctic bryophytes of 1, these analyses indicated that the minimum weight of carbon used to synthesize riccionidin A was equivalent to 1.85% of the carbon fixed by thalli during the 48 h after the abrupt increase in UVB radiation exposure.

Lipid productivity as a key characteristic for choosing algal species for biodiesel production - Melinda J. Griffiths; Susan T. L. Harrison (Journal of Applied Phycology, 2009)

Bycatch in a tropical schooling – penaeid fishery and comparisons with a related, specialised trawl regime - Q. DELL; D. T. BREWER; S. P. GRIFFITHS; D. S. HEALES; M. L. TONKS (Fisheries Management and Ecology, 2009)
The bycatch in a tropical Australian banana prawn, Penaeus merguiensis (de Man), fishery is described and contrasted with the closely related tiger prawn, Penaeus semisulcatus De Haan and Penaeus esculentus Haswell, fishery. Most of the similarity between banana prawn fishery catches was accounted for by three teleost species constituting 51.4% of the total bycatch weight. The bycatch assemblage structure of this fishery was significantly different ( P 0.05) from the adjoining tiger prawn fishery. The banana prawn fishery had a higher mean bycatch catch rate from shorter duration trawls, but lower estimated total annual bycatch (1502 t yr −1 ) than the longer duration trawls of the tiger prawn fishery (20 073 t yr −1 ). This study provides new data for quantifying bycatch and improving the accuracy of quantitative risk assessments currently being used to demonstrate sustainability of bycatch populations. The information will be incorporated into collaborative development of a long‐term monitoring programme.

Genetic variation in strains of zebrafish (Danio rerio) and the implications for ecotoxicology studies - T. S. Coe; P. B. Hamilton; A. M. Griffiths; D. J. Hodgson; M. A. Wahab; C. R. Tyler (Ecotoxicology, 2009)

Linkage mapping of CVD risk traits in the isolated Norfolk Island population - C. Bellis; H. C. Cox; T. D. Dyer; J. C. Charlesworth; K. N. Begley; S. Quinlan; R. A. Lea; S. C. Heath; J. Blangero; L. R. Griffiths (Human Genetics, 2008)

Homalanthus polyandrus (Euphorbiaceae) on Macauley Island, southern Kermadec Islands, with notes on that island's vascular flora - J. W. Barkla; P. J. Dilks; T. C. Greene; R. Griffiths (New Zealand Journal of Botany, 2008)
Homalanthus polyandrus (Kermadec poplar; Euphorbiaceae) is reported for Macauley Island, southern Kermadec Islands group. Previously this species had been reported (without a substantiating herbarium specimen) from that island by T. F. Cheeseman in 1887. In 2006 a single large tree was discovered on the western edge of the Macauley Island plateau. It is likely to have established following the eradication of feral goats in 1970 and may have arisen from bird‐dispersed seed from Raoul Island. The vegetation on Macauley Island has undergone a huge transition from a presumed earlier forested cover to the current Hypolepis dicksonioides fernland and Cyperus insularis sedgeland. A comprehensive list of all vascular plants recorded for Macauley Island is included in an appendix.

Implications of life history for genetic structure and migration rates of southern African coastal invertebrates: planktonic, abbreviated and direct development - P. R. Teske; I. Papadopoulos; G. I. Zardi; C. D. McQuaid; M. T. Edkins; C. L. Griffiths; N. P. Barker (Marine Biology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The invasion and subsequent die-off of Mytilus galloprovincialis in Langebaan Lagoon, South Africa: effects on natural communities - T. B. Robinson; C. L. Griffiths; G. M. Branch; A. Govender (Marine Biology, 2007)

Impaired hatching success and male-biased embryo mortality in Tree Sparrows - Magnus Svensson; Pekka T. Rintamäki; Tim R. Birkhead; Simon C. Griffith; Arne Lundberg (Journal of Ornithology, 2007)

Crop pathogens and other Fusarium species associated with Austrostipa aristiglumis - A. R. Bentley; T. Petrovic; S. P. Griffiths; L. W. Burgess; B. A. Summerell (Australasian Plant Pathology, 2007)

A freshwater‐feeding Lampetra fluviatilis L. population in Lough Neagh, Northern Ireland - C. E. Goodwin; D. Griffiths; J. T. A. Dick; R. W. Elwood (Journal of Fish Biology, 2006)
Pollan Coregonus autumnalis , caught in the fresh waters of Lough Neagh, Northern Ireland, were scarred by river lamprey Lampetra fluviatilis and adult river lamprey were found for much of the year with full guts, indicating a freshwater‐feeding population.

Low gene flow but high genetic diversity in the threatened Mallorcan midwife toad Alytes muletensis - F. J. L. KRAAIJEVELD‐SMIT; T. J. C. BEEBEE; R. A. GRIFFITHS; R. D. MOORE; L. SCHLEY (Molecular Ecology, 2005)
We investigated fine‐scale genetic structuring in the rare and vulnerable Mallorcan midwife toad Alytes muletensis using eight polymorphic microsatellite markers. The current range of this amphibian is restricted to some 19 sites of which six are derived from reintroductions, all located in the mountain ranges of Mallorca. We sampled tadpoles from 14 pools covering 10 natural sites and two reintroduction sites for microsatellite DNA analyses. Relatively high levels of genetic variation were found in most pools ( H E = 0.38–0.71, allelic richness = 2.6–6.2). Only at one pool has the population recently gone through a bottleneck. Dispersal between pools in different torrents does not occur whereas downstream dispersal between pools within the same torrent does happen at low frequencies. This occasional exchange of individuals does not lead to neighbouring pools in the same torrent being panmictic. This can be concluded because all F ST values (0.12–0.53) differ significantly from zero and structure analyses identified neighbouring pools as separate populations. Furthermore, assignment and migration tests showed little exchange between neighbouring pools. If upstream locations or complete torrents go extinct, they are unlikely to be recolonized naturally. For conservation purposes, reintroductions of tadpoles to sites where local extinctions have occurred may therefore be advisable.

Change in mean temperature as a predictor of extreme temperature change in the Asia–Pacific region - G. M. Griffiths; L. E. Chambers; M. R. Haylock; M. J. Manton; N. Nicholls; H.‐J. Baek; Y. Choi; P. M. Della‐Marta; A. Gosai; N. Iga; R. Lata; V. Laurent; et al. (International Journal of Climatology, 2005)
Trends (1961–2003) in daily maximum and minimum temperatures, extremes and variance were found to be spatially coherent across the Asia–Pacific region. The majority of stations exhibited significant trends: increases in mean maximum and mean minimum temperature, decreases in cold nights and cool days, and increases in warm nights. No station showed a significant increase in cold days or cold nights, but a few sites showed significant decreases in hot days and warm nights. Significant decreases were observed in both maximum and minimum temperature standard deviation in China, Korea and some stations in Japan (probably reflecting urbanization effects), but also for some Thailand and coastal Australian sites. The South Pacific convergence zone (SPCZ) region between Fiji and the Solomon Islands showed a significant increase in maximum temperature variability. Correlations between mean temperature and the frequency of extreme temperatures were strongest in the tropical Pacific Ocean from French Polynesia to Papua New Guinea, Malaysia, the Philippines, Thailand and southern Japan. Correlations were weaker at continental or higher latitude locations, which may partly reflect urbanization. For non‐urban stations, the dominant distribution change for both maximum and minimum temperature involved a change in the mean, impacting on one or both extremes, with no change in standard deviation. This occurred from French Polynesia to Papua New Guinea (except for maximum temperature changes near the SPCZ), in Malaysia, the Philippines, and several outlying Japanese islands. For urbanized stations the dominant change was a change in the mean and variance, impacting on one or both extremes. This result was particularly evident for minimum temperature. The results presented here, for non‐urban tropical and maritime locations in the Asia–Pacific region, support the hypothesis that changes in mean temperature may be used to predict changes in extreme temperatures. At urbanized or higher latitude locations, changes in variance should be incorporated. Copyright © 2005 Royal Meteorological Society.

Infrared observations and numerical modelling of grassland fires in the Northern Territory, Australia - T. L. Clark; M. J. Reeder; M. Griffiths; D. Packham; N. Krusel (Meteorology and Atmospheric Physics, 2005)

A microsatellite map of white clover - B. Barrett; A. Griffiths; M. Schreiber; N. Ellison; C. Mercer; J. Bouton; B. Ong; J. Forster; T. Sawbridge; G. Spangenberg; G. Bryan; D. Woodfield (Theoretical and Applied Genetics, 2004)

Sill dynamics and energy transformation in a jet fjord - M. Inall; F. Cottier; C. Griffiths; T. Rippeth (Ocean Dynamics, 2004)

Induction of necrotic tumor cell death by TRAIL/Apo-2L - T. J. Kemp; J.-S. Kim; S. A. Crist; T. S. Griffith (Apoptosis, 2003)

Construction and characterisation of a hexaploid wheat (Triticum aestivum L.) BAC library from the reference germplasm ‘Chinese Spring’ - S. Allouis; G. Moore; A. Bellec; R. Sharp; P. Faivre Rampant; K. Mortimer; S. Pateyron; T. N. Foote; S. Griffiths; M. Caboche; B. Chalhoub (Cereal Research Communications, 2003)

Development and Evaluation of a Macroinvertebrate Biotic Integrity Index (MBII) for Regionally Assessing Mid-Atlantic Highlands Streams - DONALD J. KLEMM; KAREN A. BLOCKSOM; FLORENCE A. FULK; ALAN T. HERLIHY; ROBERT M. HUGHES; PHILIP R. KAUFMANN; DAVID V. PECK; JOHN L. STODDARD; WILLIAM T. THOENY; MICHAEL B. GRIFFITH; WAYNE S. DAVIS (Environmental Management, 2003)

Lung Deposition and Pharmacokinetics of Cyclosporine After Aerosolization in Lung Transplant Patients - Gilbert J. Burckart; Gerald C. Smaldone; Michael A. Eldon; Raman Venkataramanan; James Dauber; Adriana Zeevi; Kenneth McCurry; Teresa P. McKaveney; Timothy E. Corcoran; Bartley P. Griffith; Aldo T. Iacono (Pharmaceutical Research, 2003)

The Irish pollan, Coregonus autumnalis : options for its conservation - C. Harrod; D. Griffiths; T. K. McCarthy; R. Rosell (Journal of Fish Biology, 2001)
The ecology of four relict Irish populations of pollan ( Coregonus autumnalis ) is compared with that of the species elsewhere, and used to advocate conservation. The threats to these populations from introduced/invasive species, habitat degradation, climate warming and commercial exploitation are summarized and the legislation governing conservation of the stocks is reviewed. Conservation options (legislation, habitat restoration, stock translocation and stock augmentation) are outlined and their practicality and efficacy considered. A preliminary search indicates that there are a number of lakes that appear to be suitable for pollan translocation.

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Sexual dimorphism in house sparrow eggs - P. J. Cordero; S. C. Griffith; J. M. Aparicio; D. T. Parkin (Behavioral Ecology and Sociobiology, 2000)

Genetic Distances Among North American, British, and West African House Fly Populations (Musca domestica L.) - E. S. Krafsur; N. L. Bryant; J. G. Marquez; N. T. Griffiths (Biochemical Genetics, 2000)

Verifying Inventory Predictions of Animal Methane Emissions with Meteorological Measurements - O. T. Denmead; R. Leuning; D. W. T. Griffith; I. M. Jamie; M. B. Esler; L. A. Harper; J. R. Freney (Boundary-Layer Meteorology, 2000)

Continuous Blood Withdrawal as a Rapid Screening Method for Determining Clearance and Oral Bioavailability in Rats - W. Griffith Humphreys; Mary T. Obermeier; Richard A. Morrison (Pharmaceutical Research, 1998)

Analgesic activity of 2-amino-4-methylpyridine, a novel NO synthase inhibitor - E. R. Pettipher; T. A. Hibbs; M. A. Smith; R. J. Griffiths (Inflammation Research, 1997)

Tenidap inhibits 5-lipoxygenase product formation in vitro, but this activity is not observed in three animal models - T. J. Carty; F. J. Sweeney; R. J. Griffiths; J. D. Eskra; M. J. Ernest; J. S. Pillar; J. D. Cheng; L. D. Loose; P. A. Joseph; P. P. Pazoles; P. F. Moore; A. Nagahisa; et al. (Inflammation Research, 1997)

Problems associated with homogeneity testing in climate variation studies: a case study of temperature in the northern Great Plains, USA - DAVID T. KEISER; JOHN F. GRIFFITHS (International Journal of Climatology, 1997)

Problems associated with homogeneity testing in climate variation studies: a case study of temperature in the northern Great Plains, USA - DAVID T. KEISER; JOHN F. GRIFFITHS (International Journal of Climatology, 1997)

Local mate competition, sex ratio and clutch size in bethylid wasps - N. T. Griffiths; H. C. J. Godfray (Behavioral Ecology and Sociobiology, 1988)